Application of the Threshold of Toxicological Concern (TTC) in Food Safety: Challenges and Opportunities - Serafimova, Rositsa; Coja, Tamara; Kass, George E. N. (Frontiers in Toxicology, 2021)
The safety assessment of chemicals added or found in food has traditionally made use of data from in vivo studies performed on experimental animals. The nature and amount of data required to carry out a risk assessment is generally stipulated either in the different food legislations or in sectoral guidance documents. However, there are still cases where no or only limited experimental data are available or not specified by law, for example for contaminants or for some minor metabolites from active substances in plant protection products. For such cases, the Threshold of Toxicological Concern (TTC) can be applied. This review explores the use of the TTC approach in food safety in the European Union in relation to the different food sectors, legal requirements and future opportunities.